Friction behavior of granite powder added brake pads - Sugozu, Ilker; Can, Ibrahim; Oner, Cengiz; Bagirov, Hanlar (Walter de Gruyter Gmbh, 2015)
Brake linings used in automotive disks are usually composed of various components. The expected properties of a brake lining are the standard values of wear resistance, friction coefficient and the economical manufacturing. Brake lining extremely warms up during braking due to friction. The braking performance of braking lining can change or the braking lining undergoes mechanical deformation due to excessive temperature. In this study, the effect of granite powder in the brake friction material on various aspects of friction characteristics were investigated. Three friction material specimens were produced based on an experimental formulation, and they contained 2, 6 and 10 % granite powder, respectively, with fixed composition of the other ingredients. Tribological properties of the friction materials were obtained using a brake dynamometer. Results showed that the friction materials containing 2 and 6 % granite powder had improved friction stability and fade resistance.
Keywords: Brake pad; granite; friction; wear